PENGARUH INSENTIF PAJAK, PEMAHAMAN PERPAJAKAN, SOSIALISASI PAJAK PADA KEPATUHAN WPOP UMKM DI MASA PANDEMI COVID-19 - Mastari, Ni Ketut Wida Asri; Jati, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Weakening MSMEs economic conditions affect MSMEs taxpayer compliance during the Covid-19 pandemic. The increase in the number of MSMEs at KPP Pratama Gianyar which is not matched by the compliance of MSMEs Individual Taxpayers (WPOP) to carry out their obligations indicates that MSMEs WPOP compliance is still low. The population in this study is MSME WPOP registered at KPP Pratama Gianyar. The sampling technique used is purposive sampling method. The number of samples determined is 100 samples. Data collection is done by distributing questionnaires directly and indirectly (via Google form). The data analysis technique used is multiple linear regression analysis.The results of the analysis show that tax incentives, understanding of taxation, and tax socialization have a positive effect on MSMEs WPOP compliance during the Covid-19 pandemic. The results of the study support the attribution theory in explaining internal and external factors that can influence a person's behavior. Tax compliance is a taxpayer's behavior that is influenced by the understanding of taxation that comes from within the taxpayer (internally), as well as the existence of tax incentives and tax socialization are external factors that influence taxpayer behavior.